1979
DOI: 10.1126/science.472741
|View full text |Cite
|
Sign up to set email alerts
|

N -Nitrosamines in the Rubber and Tire Industry

Abstract: Airborne N-nitrosomorpholine (0 to 27 micrograms per cubic meter) was found in two of four rubber industry factories. N-Nitrosodimethylamine was also found in two factories, but at lower levels. These findings may be relevant to the reported increased risk of certain types of cancer in rubber workers in some of the same areas where the N-nitrosomorpholine levels were highest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
0

Year Published

1982
1982
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(45 citation statements)
references
References 8 publications
0
45
0
Order By: Relevance
“…In September 1979 it was reported that when N-nitrosodiphenylamine (NDPA) was used in rubber compounds, other and potentially more hazardous nitrosamines could be generated. 49 In particular, it has been shown that NDPA may react with any secondary amines produced in the process to give the corresponding nitrosamine. Thus NDPA, if used with tetramethylthiuram disulphide (TMTD), may produce dimethylnitrosamine (NDMA) by nitrosation of dimethylamine.…”
Section: Cancer Mortality Analysismentioning
confidence: 99%
“…In September 1979 it was reported that when N-nitrosodiphenylamine (NDPA) was used in rubber compounds, other and potentially more hazardous nitrosamines could be generated. 49 In particular, it has been shown that NDPA may react with any secondary amines produced in the process to give the corresponding nitrosamine. Thus NDPA, if used with tetramethylthiuram disulphide (TMTD), may produce dimethylnitrosamine (NDMA) by nitrosation of dimethylamine.…”
Section: Cancer Mortality Analysismentioning
confidence: 99%
“…On the basis of the available data, it was determined that there is evidence of an excess of lung cancer among workers who have ever been employed in the Hilling and Tuber area of B.F. Goodrich 8,1986 we sent letters to the company and union informing them of the progress of the study.…”
Section: Discussionmentioning
confidence: 99%
“…They may be synthesized in the environment and in the body. Occupational exposures may occur, for example, to machinists from synthetic grinding fluids, and in industries such as leather tanneries and tire manufacturing plants (1,2). Non-occupational exposure also may occur from such sources as beer, cured meats, cosmetics, and tobacco smoke.…”
Section: Methodsmentioning
confidence: 99%